Effects of topography and anthropogenic alterations in forest environments on the breeding use by two endangered frog species in amami-oshima Island. Issue 3 (4th May 2021) - Iwai, Noriko
ABSTRACT: Amphibians are among the most threatened taxa in the world. Anthropogenic habitat alteration is possibly the most important driver of their population decline and can occur through many different factors. To develop effective conservation measures when multiple factors are involved, we need to know the relative impact of each factor. I aimed to reveal breeding site choice by two endangered frog species ( Babina subaspera and Odorrana splendida ) in the subtropical forests of Amami-Oshima Island, where multiple anthropogenic factors are expected to have effects on the forest environment. I analyzed the breeding use by the two species with nine topographic and three anthropogenic (forest age, forest road density, and density of invasive mongoose) variables, using random forest analysis. The critical variable for determining the breeding use by B. subaspera was the size of upstream contributing area (UCA), followed by topographic wetness index (TWI) and altitude, while that for O. splendida was altitude, followed by UCA, and TWI. The importance of anthropogenic variables was less than that of topographic variables and was greatest for forest age and lowest for mongoose density. Forest sites less than 40 years old, with more roads within a 500 m buffer, and with a higher mongoose density showed a low probability of the frog's presence. The peculiar topographical requirements of the two frog species for breeding may be the reason for the relatively small impact of anthropogenic variables compared to topographic variables.